Long-Term Memory Updating: The Reset-of-Encoding Hypothesis in List-Method Directed Forgetting - Pastötter, Bernhard; Tempel, Tobias; Bäuml, Karl-Heinz T. (Frontiers in Psychology, 2017)
People’s memory for new information can be enhanced by cuing them to forget older information, as is shown in list-method directed forgetting (LMDF). In this task, people are cued to forget a previously studied list of items (list 1) and to learn a new list of items (list 2) instead. Such cuing typically enhances memory for the list 2 items and reduces memory for the list 1 items, which reflects effective long-term memory updating. This review focuses on the reset-of-encoding (ROE) hypothesis as a theoretical explanation of the list 2 enhancement effect in LMDF. The ROE hypothesis is based on the finding that encoding efficacy typically decreases with number of encoded items and assumes that providing a forget cue after study of some items (e.g., list 1) resets the encoding process and makes encoding of subsequent items (e.g., early list 2 items) as effective as encoding of previously studied (e.g., early list 1) items. The review provides an overview of current evidence for the ROE hypothesis. The evidence arose from recent behavioral, neuroscientific, and modelling studies that examined LMDF on both an item and a list level basis. The findings support the view that ROE plays a critical role for the list 2 enhancement effect in LMDF. Alternative explanations of the effect and the generalizability of ROE to other experimental tasks are discussed.